The politics of development co-operation : NGOs, gender and partnership in Kenya - Aubrey, Lisa Marie, 1961- (Routledge studies in development and society ;, 1997)
Focusing on Kenya, and in particular on Maendeleo Ya Wanawake (MYWO), this book examines politics of inter-organizational development co-operation, examining issues of power, autonomy, and dependence.